2013
DOI: 10.7314/apjcp.2013.14.3.1905
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Clinical Variables Account for Changes in Health-related Quality of Life and Symptom Burden as Treatment Outcomes in Colorectal Cancer: A Longitudinal Study

Abstract: Objective: The aim of the current study was to evaluate changes in treatment outcomes in terms of healthrelated quality of life (HRQoL) and symptom burden at zero, one, three, and six months after an initial diagnosis of colorectal cancer. The demographic and clinical characteristics that account for outcome changes in patients were investigated using a repeated measures framework. Methods and Materials: A cohort study was performed of 134 colorectal cancer patients followed from diagnosis to 6 months post-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Educational level, educational level of the spouse, job status, current financial problems, residence outside Amman, presence of migraine, ability to perform daily activities, pathological coding, cancer recurrence, type of surgery, radiation therapy, stoma use, loss of appetite, reported diarrhea symptom and HADS score were also important predictors of the quality of life scores for QLQ-C30 and QLQ-CR29. These are consistent with results from other countries (Tsunoda et al, 2007;Gray et al, 2011;Hung et al, 2013). Results from the UK showed that sex, stage of the disease, symptoms, beliefs about consequences, lower income and presence of other comorbidities were the main predictors for the quality of life scores (Gray et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Educational level, educational level of the spouse, job status, current financial problems, residence outside Amman, presence of migraine, ability to perform daily activities, pathological coding, cancer recurrence, type of surgery, radiation therapy, stoma use, loss of appetite, reported diarrhea symptom and HADS score were also important predictors of the quality of life scores for QLQ-C30 and QLQ-CR29. These are consistent with results from other countries (Tsunoda et al, 2007;Gray et al, 2011;Hung et al, 2013). Results from the UK showed that sex, stage of the disease, symptoms, beliefs about consequences, lower income and presence of other comorbidities were the main predictors for the quality of life scores (Gray et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Distress was rated using a 5-point Likert scale (i.e., 0= not at all, 1= mild, 2= moderate, 3= severe, 4= very severe) (41). The validity and reliability of the MSAS are well established (41)(42)(43).…”
Section: Instrumentsmentioning
confidence: 99%
“…Since then it has undergone several revisions and further developments (Osoba et al, 1997). This questionnaire is frequently used in cancer of the colorectum (Hung et al, 2013;Smith et al, 2013). The questionnaire has been validated across many cultures and disease conditions and was found to have adequate acceptable psychometric properties (Schwenk et al, 2004;Huang et al, 2007;Jayasekara et al, 2008;Luckett et al, 2011;Uwer et al, 2011;Yakar and Pinar, 2013).…”
Section: Introductionmentioning
confidence: 99%